2019
DOI: 10.1128/mbio.01032-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pneumococcal Factors Affecting Pneumococcal Shedding Shows that the dlt Locus Promotes Inflammation and Transmission

Abstract: Host-to-host transmission is a necessary but poorly understood aspect of microbial pathogenesis. Herein, we screened a genomic library of mutants of the leading respiratory pathogen Streptococcus pneumoniae generated by mariner transposon mutagenesis (Tn-Seq) to identify genes contributing to its exit or shedding from the upper respiratory tract (URT), the limiting step in the organism’s transmission in an infant mouse model. Our analysis focused on genes affecting the bacterial surface that directly impact in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 92 publications
(100 reference statements)
0
44
0
Order By: Relevance
“…We hypothesize this gene is maintained because its deletion is associated with increased sensitivity to antimicrobial peptides and thus reduces fitness in niches with significant inflammatory infiltrate, such as the pneumonic lung. In addition, recent studies have also demonstrated a role of dltB in pneumococcal transmission whereby mutants in this locus have significantly reduced shedding from colonized mice which reduces mammalian transmission 10 . The increased adhesion and colonization phenotypes conferred by loss of this locus may initially be beneficial, but the failure to transmit to new hosts may explain the retention of this gene in S. pneumoniae given the fitness advantages we observe during colonization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize this gene is maintained because its deletion is associated with increased sensitivity to antimicrobial peptides and thus reduces fitness in niches with significant inflammatory infiltrate, such as the pneumonic lung. In addition, recent studies have also demonstrated a role of dltB in pneumococcal transmission whereby mutants in this locus have significantly reduced shedding from colonized mice which reduces mammalian transmission 10 . The increased adhesion and colonization phenotypes conferred by loss of this locus may initially be beneficial, but the failure to transmit to new hosts may explain the retention of this gene in S. pneumoniae given the fitness advantages we observe during colonization.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the major selective pressures on the pneumococcus, as invasive disease is typically envisioned as an evolutionary dead-end due to clearance by the immune system or antibiotics or via the death of the host, thereby preventing further transmission of the strain. As such, the pneumococcus has evolved numerous strategies to facilitate efficient transmission and colonization of new hosts [8][9][10][11][12][13] . Mutational screens have identified many pneumococcal genes that are required for successful colonization of the nasal passages as well as for invasive infection of the lungs and the bloodstream 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance between transmissibility and within-host fitness parallels an invasion-persistence trade-off in other organisms—some genotypes may more readily disperse and colonize new hosts/territories, but are less persistent and thus fare poorly when present in the same environment as less dispersable but more competitive genotypes. This trade-off is evident in several S. pneumoniae genes, such as toxin pneumolysin [40, 41], capsule serotype (for example, serotype 4 compared to 23F) [40, 42], and the aforementioned dltB [30, 43], which promote transmissibility at the expense of within-host fitness. Whether these genes are favored by selection and maintained depends on the relative importance of transmissibility and within-host fitness, as shown by the loss of dltB in serial passage where transmission is more certain.…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall modifications in pneumococci can be triggered by AMPs. Treatment with lysozyme leads to upregulation of the dlt locus through the CiaRH sensoring system, resulting in lipoteichoic acid (LTA) modifications and increased inflammatory responses, which in that case contributed to bacterial shedding and transmission (Zafar et al, 2019). Thus, D-alanylation of the cell wall -a mechanism of AMP resistance shared among different Gram-positive microbes-can be induced, in pneumococci, by treatment with antimicrobial proteins that target the bacterial cell wall.…”
Section: Amp Induced Gene Expression/repressionmentioning
confidence: 99%